Studies on Effect of Some Medicinal Plants on Pancreatic Lipase Activity using Spectrophotometric Method - Gowadia, Neha; Vasudevan, T.N. (Asian Journal of Chemistry, 2010)
Forty medicinal plants were studied for their effect on pancreatic lipase activity. The method involves the prior incubation of enzyme with 10% w/v aqueous decoction of plant drug. The enzyme activity was assayed by colorimetry at 710 om. Percentage activation or inhibition of enzyme by plant extract was calculated by comparing the activity of pancreatic lipase in presence and absence of plant extract. Results of studies showed that Eugenia caryophyllus, Mesua Jerea, Terminalia belerica, Terminalia chebula, Swertia chirata, Witlzania somnifera have significant inhibitory effect on the activity of enzyme. Tribulus terrestris and Picrasma excelsa showed activation of enzyme activity.